Painting in Tempera, c. 1900 - Gómez González, Marisa (Ge-conservacion, 2018)
Painting in Tempera, c. 1900Karoline Beltinger (SIK-ISEA), Zurich & Jillen Nadolny (Art Analysis & Research) London eds.Publicado por Schweizerisches Institut für Kunstwissenschaft (SIK-ISEA) y Archetype Publications Ltd2016ISBN: 9781909492448Dimensiones: 297 x 210Páginas: 264Ilustraciones en color